Cowpea Leaves: Feasible Solutions to Overcome Seasonal Availability - Owade, Joshua; Abong', George; Okoth, Michael; Mwangombe, Agnes (Academia Kenya, 2021)
Cowpea leaves (Figure 1) is the most produced ALV in the country and has been promoted as a food security crop due to its rich micronutrient content (Owade et al., 2020). However, seasonal availability of the crop constrains its extensive utilization. Moreover, during the long and short rains in ASALs, the vegetables is in abundance but this is followed by scarcity in the off-season. The leafy vegetable has been promoted over the grains of the crop as a cheap alternative source of micronutrients (Mamiro et al., 2011). Value addition of fresh produce is deployed for product diversification and postharvest management of produce. Without postharvest management, Gogo et al. (2017), reports economic losses of 12.6–34.4%, further limiting vegetable availability for household utilization and commercialization. Policy gaps with regards to cowpea leaves in the country are evident due to limited policy focus of this value chain as there is limited documentation of the postharvest losses of any vegetable in the African Postharvest Losses Information System.
Keywords: Agriculture; Cowpea; Kenya